Early Childhood School Governance Conflict Management Perspective - Mahsur (Edumaspul: Jurnal Pendidikan, 2026)
Effective PAUD school governance requires managerial competence that is not limited to planning, implementation, and evaluation, but also includes conflict management within the educational setting. Conflicts in PAUD commonly arise from differences in perception among school principals, teachers, staff, parents, and the community regarding policies, communication, task distribution, and resource management. This article aims to analyze PAUD school governance from a conflict management perspective by emphasizing participatory leadership, effective communication, mediation, collaboration, and a harmonious organizational culture. This paper employs a literature review approach by examining literature on PAUD management, educational governance, and conflict resolution strategies in schools. The findings indicate that sound conflict management strengthens PAUD governance by creating a conducive work climate, increasing trust among school members, and optimizing early childhood education services. Therefore, conflict management is not merely a problem-solving tool, but an integral part of professional, accountable, and quality-oriented PAUD governance. Abstrak Tata kelola sekolah PAUD yang efektif membutuhkan kompetensi manajerial yang tidak hanya terbatas pada perencanaan, implementasi, dan evaluasi, tetapi juga mencakup manajemen konflik dalam lingkungan pendidikan. Konflik dalam PAUD umumnya muncul dari perbedaan persepsi di antara kepala sekolah, guru, staf, orang tua, dan masyarakat mengenai kebijakan, komunikasi, pembagian tugas, dan pengelolaan sumber daya. Artikel ini bertujuan untuk menganalisis tata kelola sekolah PAUD dari perspektif manajemen konflik dengan menekankan kepemimpinan partisipatif, komunikasi yang efektif, mediasi, kolaborasi, dan budaya organisasi yang harmonis. Makalah ini menggunakan pendekatan tinjauan pustaka dengan meneliti literatur tentang manajemen PAUD, tata kelola pendidikan, dan strategi penyelesaian konflik di sekolah. Temuan menunjukkan bahwa manajemen konflik yang baik memperkuat tata kelola PAUD dengan menciptakan iklim kerja yang kondusif, meningkatkan kepercayaan di antara anggota sekolah, dan mengoptimalkan layanan pendidikan anak usia dini. Oleh karena itu, manajemen konflik bukan hanya alat pemecahan masalah, tetapi merupakan bagian integral dari tata kelola PAUD yang profesional, akuntabel, dan berorientasi pada kualitas.